Vitamin D: A Potential Star for Treating Chronic Pancreatitis - Zheng, Meifang; Gao, Runping (Frontiers in Pharmacology, 2022)
Chronic pancreatitis (CP) is a chronic inflammatory and fibrotic disease of the pancreas. The incidence of CP is increasing worldwide but the effective therapies are lacking. Hence, it is necessary to identify economical and effective agents for the treatment of CP patients. Vitamin D (VD) and its analogues have been confirmed as pleiotropic regulators of cell proliferation, apoptosis, differentiation and autophagy. Clinical studies show that VD deficiency is prevalent in CP patients. However, the correlation between VD level and the risk of CP remains controversial. VD and its analogues have been demonstrated to inhibit pancreatic fibrosis by suppressing the activation of pancreatic stellate cells and the production of extracellular matrix. Limited clinical trials have shown that the supplement of VD can improve VD deficiency in patients with CP, suggesting a potential therapeutic value of VD in CP. However, the mechanisms by which VD and its analogues inhibit pancreatic fibrosis have not been fully elucidated. We are reviewing the current literature concerning the risk factors for developing CP, prevalence of VD deficiency in CP, mechanisms of VD action in PSC-mediated fibrogenesis during the development of CP and potential therapeutic applications of VD and its analogues in the treatment of CP.